Adaptive Moving Sliding Mode Control for SISO Systems: Application to an Electropneumatic System - Assil Ayadi; Soufien Hajji; Mohamed Smaoui; Abdessattar Chaari (Journal of Control Science and Engineering)
This paper aims to propose and develop an adaptive moving sliding mode controller (AMSMC) that can be applied for nonlinear single-input single-output (SISO) systems with external disturbances. The main contribution of this framework consists to overcome the chattering phenomenon problem. The discontinuous term of the classic sliding mode control is replaced by an adaptive term. Moreover, a moving sliding surface is proposed to have better tracking and to guarantee robustness to the external disturbances. The parameters of the sliding surface and the adaptive law are deduced based on Lyapunov stability analysis. An experimental application of electropneumatic system is treated to validate the theoretical results.